2010
DOI: 10.1007/s12633-010-9055-6
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Based Nanocoatings on Metal Alloys and Their Role in Surface Engineering

Abstract: Metals and their alloys have been widely used in all aspects of science and engineering. However the science of nanotechnology is driving newer demands and requirements for better performance of existing materials and also at a higher level of precision. This is naturally presenting complicated demands on the surface of these metals with a need for surface modification. Self Assembled Monolayers (SAMs) are nanosized coatings that present the most efficient method of carrying out surface modification. Alkylsila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 485 publications
0
7
0
Order By: Relevance
“…[17][18][19] Silanes or phosphonates are suitable compounds for those metallic surfaces that are spontaneously covered by their oxides such us Ti, Al, Hf, Zn, Sn, Mg alloys, steel and Ni alloys. 18,[20][21][22][23][24][25][26][27][28][29][30] The terminal OH groups of the oxihydroxide metallic surface react with silanes that undergo hydrolysis forming polysiloxane (Si-O-Si) bonds and Si-O-substrate bonds. 31,32 The formation of a robust bond of the silanes with the substrate confers a strong stability to the layer and allows further chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Silanes or phosphonates are suitable compounds for those metallic surfaces that are spontaneously covered by their oxides such us Ti, Al, Hf, Zn, Sn, Mg alloys, steel and Ni alloys. 18,[20][21][22][23][24][25][26][27][28][29][30] The terminal OH groups of the oxihydroxide metallic surface react with silanes that undergo hydrolysis forming polysiloxane (Si-O-Si) bonds and Si-O-substrate bonds. 31,32 The formation of a robust bond of the silanes with the substrate confers a strong stability to the layer and allows further chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The Si–C bond, with a substantial bond energy of ∼377 kJ/mol, is ubiquitous in organic reaction synthesis, in natural product synthesis, and in the preservation of the stereochemistry in complex organic molecules . Due to their stability, alkylsilanes are used in a variety of industries including the electrical, electronics, and aeronautical industries and are also promising surfactants in the production of the nanostructured surfaces needed for making complex macroassemblies . Early in the development of the chemistry of methylsilicon phthalocyanines, however, it was observed that while the Si–C bond in these compounds is stable to heat, it is readily photolyzed by near-infrared light in solution, which was utilized synthetically by Kenney and co-workers for developing the photodynamic therapy (PDT) candidate Pc 4, a silicon phthalocyanine bearing two axial ligands consisting of a hydroxyl group and a silylalkyl amine .…”
Section: Introductionmentioning
confidence: 99%
“…SAMs are a versatile tool to carry out surface modifications[22-24]. They are structures formed by the spontaneous chemisorption of surfactant molecules on surfaces and are typically in the size range of 1-3 nm.…”
Section: Introductionmentioning
confidence: 99%